EXPERIMENTS ON THE RELATIONSHIP BETWEEN PERDE AND SEYIR IN TURKISH MAKAM MUSIC - Akkoc, Can; Sethares, William A.; Karaosmanoglu, M. Kemal (UNIV CALIFORNIA PRESS, 2015)
WHEN I WAS A KID, THE ELDERS IN THE VILLAGE COULD TELL THE MAKAM OF A PIECE JUST BY LISTENING. While interviewing performers, enthusiasts, and experts in traditional Turkish taksims (improvisations), variations of this comment were made many times. Some of the respondents claimed to be able to identify the makam of a taksim, but others believed that this ability might now be a lost art. This paper documents a series of experiments (based on caricaturized or skeletonized taksim-like creations) designed to determine if it is possible to identify the makam from purely acoustical features, and, when possible, to determine the relative importance of the various audible features that may be used to establish the makam. Two basic classes of features are investigated: perde (the set of pitches used in the performance) and seyir (which relates to temporal motion within the piece, for instance, repetitive or common motives or melodic contour). The experiments provide evidence that both kinds of features contribute to the ability to recognize makams. Experiments that randomize the order of events show that pitch cues (perde) are often adequate to allow accurate identification of the makam. In experiments where both pitch and temporal cues are present but conflict (for example, a piece in which the perde is chosen from one makam and the seyir from another), experts often favor the temporal information.
Keywords: Turkish makam recognition; AEU system; recognition of scale and key by experts; motif in Turkish music; taksim (improvisation); TONAL HIERARCHIES; Music; Psychology